2009
DOI: 10.1016/j.immuni.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Insights into MHC Class I Peptide Loading from the Structure of the Tapasin-ERp57 Thiol Oxidoreductase Heterodimer

Abstract: SUMMARY Tapasin is a glycoprotein critical for loading Major Histocompatibility Complex (MHC) class I molecules with high affinity peptides. It functions within the multimeric peptide-loading complex (PLC) as a disulfide-linked, stable heterodimer with the thiol oxidoreductase ERp57, and this covalent interaction is required to support optimal PLC activity. Here we present the 2.6 Å resolution structure of the tapasin/ERp57 core of the PLC. The structure reveals the basis for the stable dimerization of tapasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
352
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(369 citation statements)
references
References 54 publications
15
352
1
1
Order By: Relevance
“…The N-terminal domain of tapasin is essential for association and peptide loading of MHC class I (11). By comparing the sequences of tapasin from different species and screening mutant tapasin molecules, Dong et al (12) identified a region of the N-terminal domain of tapasin that interacts with MHC class I. This cluster of residues on tapasin includes E185, R187, Q189, H190, L191, K193, L250, and Q261 defined by the panel of tapasin TN mutants (TN3, TN4, TN5, TN6, TN7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal domain of tapasin is essential for association and peptide loading of MHC class I (11). By comparing the sequences of tapasin from different species and screening mutant tapasin molecules, Dong et al (12) identified a region of the N-terminal domain of tapasin that interacts with MHC class I. This cluster of residues on tapasin includes E185, R187, Q189, H190, L191, K193, L250, and Q261 defined by the panel of tapasin TN mutants (TN3, TN4, TN5, TN6, TN7).…”
mentioning
confidence: 99%
“…This cluster of residues on tapasin includes E185, R187, Q189, H190, L191, K193, L250, and Q261 defined by the panel of tapasin TN mutants (TN3, TN4, TN5, TN6, TN7). This region of tapasin is predicted to bind a loop consisting of residues 128-136 below the a2-1 helix of the MHC class I heterodimer (12)(13)(14)(15). Residues in the predicted contact site in MHC class I (e.g., T134) are essential for incorporation of MHC class I into the peptide loading complex and efficient peptide loading (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Exclusion of the exon 3 encoded region (tpn residues 50-137) interrupts the structure of the shorter N-terminal stalk found in the L-shaped form of tpn [36]. Cys-95, forming a covalent bond with the oxidoreductase ERp57 [29] is therefore lost, whereas the C-terminal structure should remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tpn transmembrane/cytosolic region and the tpn C-terminal Ig-like domain, a structure which should be retained in TPSN Ex3, contribute to the efficiency of tpn to interact with MHC-I [39]. Several contact sites for MHC-I on tpn have recently been defined [36], of these only Glu-72 is missing in TPSN Ex3, which could be the reason for the loss of stable TPSN Ex3-MHC-I interaction. Also, Roder et al [22] demonstrated that the first 87 residues of tpn are sufficient to stabilize MHC-I and peptide loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation